Vietnam tourism occupational skills standards in Western food preparation / Vietnam national administration of tourism - Vietnam national administration of tourism
The VTOS standards, which are one of the key outputs of the project, have been developed in 13 disciplines at entry level as follows: hotel security, front office, housekeeping, F&B service, Western food preparation, bakery/pastry, Vietnam cuisine, CRS for hotels, small hotel management, travel operations, tour operations, CRS for travel, tour guiding.